2009
DOI: 10.1080/00288230909510524
|View full text |Cite
|
Sign up to set email alerts
|

Field radiometer with canopy pasture probe as a potential tool to estimate and map pasture biomass and mineral components: A case study in the Lake Taupo catchment, New Zealand

Abstract: Precision farming requires data on resource status at a very fine, within-paddock scale which is impractical to collect by traditional sampling methods. This paper demonstrates the potential of a field radiometer in conjunction with a canopy pasture probe (CAPP) and global positioning system (GPS) to predict and map the spatial distribution patterns of herbage biomass and mass of nutrients, such as nitrogen (N), phosphorous (P), potassium (K), and sulphur (S) in hill country A08070; Online publication date 4 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…They suggested that using mobile-sensor-based biomass estimation methods could be an effective alternative to the traditional clipping method for a rapid and accurate in-field biomass estimation. Different types of sensors both in static and mobile application have been used in recent grassland studies (Numata et al, 2008;Biewer et al, 2009a, b;Himstedt et al, 2009;Kawamura et al, 2009;Fricke et al, 2011;Pullanagari et al, 2012;Duan et al, 2014;Rahman et al, 2014;Reddersen et al, 2014). Particularly hyperspectral sensors, which measure reflectance signals over a wide range of wavelengths in discrete bands of 1-15 nm width, have raised considerable interest for the prediction of biomass and quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that using mobile-sensor-based biomass estimation methods could be an effective alternative to the traditional clipping method for a rapid and accurate in-field biomass estimation. Different types of sensors both in static and mobile application have been used in recent grassland studies (Numata et al, 2008;Biewer et al, 2009a, b;Himstedt et al, 2009;Kawamura et al, 2009;Fricke et al, 2011;Pullanagari et al, 2012;Duan et al, 2014;Rahman et al, 2014;Reddersen et al, 2014). Particularly hyperspectral sensors, which measure reflectance signals over a wide range of wavelengths in discrete bands of 1-15 nm width, have raised considerable interest for the prediction of biomass and quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In situ collected vegetation spectra have been found to be a time-saving, non-destructive and cost-effective alternative to laboratory analysis (Curran, 1989). The approach has been successfully applied in various biomes, including temperate grasslands (Biewer et al, 2009b;Kawamura et al, 2009;Sanches et al, 2013) and subtropical grasslands (Knox et al, 2011(Knox et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is an important macro element in animal nutrition (Reid et al, 2015) and has therefore been investigated by several authors (e.g. Albayrak et al, 2011;Kawamura et al, 2009). Apart from nitrogen and phosphorus, Mutanga et al (2004) used in situ measured hyperspectral reflectance data to model potassium, calcium and magnesium concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of plant physiological parameters and structures including leaf area index, biomass, water, pigment and nutrient content, crop canopy, and density have been investigated extensively (Kawamura et al, 2009;Mü ller et al, 2008;Ray, Singh, and Panigrahy, 2010).…”
Section: Introductionmentioning
confidence: 99%